PERILAKU MASYARAKAT DALAM MENGHADAPI PANDEMI COVID-19 DI DESA TINAMBUNG KECAMATAN PAMBOANG SULAWESI BARAT - Togubu, Dian Mirza; Musfirah, Musfirah; Sulfiani, Sulfiani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Corona virus is a a zoonotic disease or virus that originates from animals and can be transmitted to humans. Indonesia is ranked as the 23rd highest case in the world with a total of 116,871 cases. West Sulawesi Province is an area affected by COVID-19 with a total of 241 positive cases. The purpose of this study was to find out in depth about the behavior of the community in dealing with the COVID-19 pandemic in Tinambung Village, Pamboang District. Held from June to July 2020 in Tinambung Village, Pamboang District, West Sulawesi Province. This study uses a qualitative research method with a case study approach. The technique used is in-depth interview and observation. The results found in Tinambung Village showed that community knowledge related to COVID-19 reached the level of understanding and only a few people reached the level of knowing. The attitude of the people, accepting the appeals and rules during the COVID-19 pandemic, however decreased when the government issued a new normal policy. As for the implementation of physical distancing, it is still not maximally applied in public places such as markets and at events such as weddings, thanksgiving and takziah. The role of the village government is quite active in anticipating the transmission of COVID-19 in Tinambung Village, including spraying disinfectants, distributing masks and providing a place to wash hands. Suggestions that the government should be careful and not in a hurry to provide terms and policies without conducting counseling or education first to the community